Kesan Penggunaan Ujian Adaptif Berkomputer Terhadap Kebimbangan Kepada Ujian Matematik Dan Sikap Terhadap Ujian Adaptif Berkomputer - Ikthsar, Iylia Syazwani Jamil (2018)
Testing modes does influence the students in term of anxiety and attitude. The purpose of this study was to explore the influence of different test modes on anxiety towards examination, anxiety towards mathematics and attitude towards computer. Beside that, in the process of development of Computerized Adaptive Testing (CAT), the psychometric properties of items were explored and studied. This study also looking at the readiness of Malaysian Polytechnic students in answering basic algebra test through CAT. This research was conducted in three stages including creating an item bank, designing a CAT and analyzing questionnaires regarding anxiety towards examinations, anxiety towards mathematics and attitude towards computer and attitude towards CAT. 1080 multiple-choice items on chapter one, Engineering Mathematics 1 were created for an item bank to be used in stage two. The item bank consisted of five parts which is; simplification of Algebraic fractions; solving algebraic fractions; conversion of formulas; solving quadratic equations and solving simultaneous linear equation with two variables. 36 sets of papers with 35 items each, containing 25 unique items and 10 common items, were administered to 1464 diploma level students, engineering course from four different polytechnics. The data were analyzed using the Rasch Model to get the item that fit the model and the difficulty levels of each items. In the second stage, CAT was created, tested and modified after trials. 300 students from three polytechnics answered CAT, Computer-Based Test (CBT) and Traditional Paper and Pencil test in a Quasi-Experiment. The output of this study show that the Malaysian polytechnic students are ready for CAT. CAT also manage to decrease the level of anxiety towards examination and mathematics. Beside that, attitude towards computer amongs Malaysian polytechnic students becoming more positive after sit for CAT.